1993
DOI: 10.2165/00003088-199325010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interactions with ACE Inhibitors

Abstract: Angiotensin converting enzyme (ACE) inhibitors which have active moieties excreted mainly in urine require adjustment of either the dose or the interval between doses in patients with moderate to severe renal dysfunction or severe congestive heart failure. Those agents such as temocapril (CS 622) and fosinopril, excreted both in urine and bile, may not require such adjustment. Renal clearance of ACE inhibitors may be reduced and some accumulation may occur in elderly patients with mild renal dysfunction or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 155 publications
0
29
0
Order By: Relevance
“…Thus, it was considered that the concomitant use of simvastatin and lovastatin possibly attenuates the drug efficacy of ACE inhibitors via CES1A inhibition. However, in contrast to that in vitro study, the lack of interaction in vivo in human between enalapril and simvastatin (Shionoiri, 1993) and between ramipril and simvastatin was reported (Meyer et al, 1994). In vivo drug-drug interactions can be quantitatively predicted by comparing the maximum value of the unbound concentration at the inlet to the liver (I inlet, u, max ) estimated using pharmacokinetic data and the value of K i obtained in vitro (Ito et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, it was considered that the concomitant use of simvastatin and lovastatin possibly attenuates the drug efficacy of ACE inhibitors via CES1A inhibition. However, in contrast to that in vitro study, the lack of interaction in vivo in human between enalapril and simvastatin (Shionoiri, 1993) and between ramipril and simvastatin was reported (Meyer et al, 1994). In vivo drug-drug interactions can be quantitatively predicted by comparing the maximum value of the unbound concentration at the inlet to the liver (I inlet, u, max ) estimated using pharmacokinetic data and the value of K i obtained in vitro (Ito et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…We also found that diltiazem and verapamil (K i 9.0 6 0.5 mM and 16.0 6 1.1 mM, respectively) were weaker than simvastatin at inhibiting CES1 hydrolysis of TPL. Little or no clinical interactions have been demonstrated between EPL/RPL and simvastatin (Shionoiri, 1993;Meyer et al, 1994); therefore, these drugs might also possess a low potential for affecting the pharmacokinetics of ACE inhibitors. However, with the lengthening list of CES1 substrates and inhibitors, the possibility of clinically significant interactions has increased for scenarios in which several of these drugs are administered concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytopaenia occurs after combined therapy of ACE inhibitors and interferones [37]. ACE inhibitors interact with different drugs, like NSAIDs [38]. Cytokines antagonize the hypotensive effect of ACE inhibitors [39]; severe hypokalaemia occurs with potassium-depleting diuretics [40] and potassium-sparing diuretics produce hyperkalaemia [41,42].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…ACE inhibitors interact with different drugs, like NSAIDs [38]. Cytokines antagonize the hypotensive effect of ACE inhibitors [39]; severe hypokalaemia occurs with potassium-depleting diuretics [40] and potassium-sparing diuretics produce hyperkalaemia [41,42]. ACE inhibitors were shown to increase potassium levels in the body [43].…”
Section: Drug Interactionsmentioning
confidence: 99%